Effects of dietary interventions on depressive symptom profiles: results from the MooDFOOD depression prevention study. Issue 15 (7th November 2022) - Vreijling, Sarah R.; Penninx, Brenda W. J. H.; Bot, Mariska; Watkins, Ed; Owens, Matthew; Kohls, Elisabeth; Hegerl, Ulrich; Roca, Miquel; Gili, Margalida; Brouwer, Ingeborg A.; Visser, Marjolein; Beekman, Aartjan T. F.; et al.
Abstract: Background: Dietary interventions did not prevent depression onset nor reduced depressive symptoms in a large multi-center randomized controlled depression prevention study (MooDFOOD) involving overweight adults with subsyndromal depressive symptoms. We conducted follow-up analyses to investigate whether dietary interventions differ in their effects on depressive symptom profiles (mood/cognition; somatic; atypical, energy-related). Methods: Baseline, 3-, 6-, and 12-month follow-up data from MooDFOOD were used ( n = 933). Participants received (1) placebo supplements, (2) food-related behavioral activation (F-BA) therapy with placebo supplements, (3) multi-nutrient supplements (omega-3 fatty acids and a multi-vitamin), or (4) F-BA therapy with multi-nutrient supplements. Depressive symptom profiles were based on the Inventory of Depressive Symptomatology. Results: F-BA therapy was significantly associated with decreased severity of the somatic ( B = −0.03, p = 0.014, d = −0.10) and energy-related ( B = −0.08, p = 0.001, d = −0.13), but not with the mood/cognition symptom profile, whereas multi-nutrient supplementation was significantly associated with increased severity of the mood/cognition ( B = 0.05, p = 0.022, d = 0.09) and the energy-related ( B = 0.07, p = 0.002, d = 0.12) but not with the somatic symptom profile. Conclusions: Differentiating depressive symptom profiles indicated that food-related behavioral interventions are most beneficial to alleviate somatic symptoms and symptoms of the atypical, energy-related profile linked to an immuno-metabolic form of depression, although effect sizes were small. Multi-nutrient supplements are not indicated to reduce depressive symptom profiles. These findings show that attention to clinical heterogeneity in depression is of importance when studying dietary interventions.